THE DYNAMICS OF THE FORM OF NUSANTARA MOSQUE: ARCHITECTURAL HOMOGENEITY VIS A VIS ARCHITECTURAL HYBRIDITY - Wismantara, Pudji Pratitis (Journal of Islamic Architecture, 2012)
There are two points of departure in the design of mosque architecture in Nusantara, namely architectural homogeneity and architectural hybridity. Each provides the legitimacy of the architecture of identity formation. This paper seeks to explore the comparative, the concept of homogeneity and hybridity architecture, with a critical theory approach. TheÂ  results of this search is, the concept of architectural homogeneity establishing assumption that certain architectural forms are supposed to represent "universal identity and modernity" of Muslim architecture. Meanwhile, the concept of architectural hybridity to show enrichment architecture identity because of the attempt to combine aspects of the universality of Islam with locality of Nusantara. Both these aspects can be positioned as the two subjects of mutual dialogue in a parallel position. As architecture strategy, the concept of hybridity reflects the effort or ijtihad in interpreting local and universal contextuality in the contemporary conditions that are constantly evolving and open.Keywords: Nusantara mosque, hybridity of architecture, homogeneity of architecture, architecture strategy